1979
DOI: 10.1002/jsfa.2740301003
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical basis of insect resistance in Vigna unguiculata

Abstract: The bruchid beetle Callosobruchus maculatus (F.) causes extensive damage to seeds of the cowpea, Vigna unguiculata (L.) (Walp.), when this important tropical foodstuff is stored. A variety of cowpea resistant to attack by this pest has been described. In the present work seeds of a number of cowpea varieties, including the resistant one, were tested for the presence of a physical resistance to C. maculatus, in terms of repulsion of oviposition or of failure of larvae to enter the seeds. No evidence to suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
1
8

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(76 citation statements)
references
References 22 publications
2
61
1
8
Order By: Relevance
“…In the 1970's, screening of the cowpea germplasm collection at the International Institute of Tropical Agriculture (Ibadan, Nigeria), allowed the identification of the first genotype highly resistant to C. maculatus, the cultivar TVu 2027 (Gatehouse et al, 1979), from which several other lineages such as IT81D-1032, IT81D-1053, IT81D-1045, and IT81D-1064 show different levels of resistance to the cowpea beetle were bred. The observed antibiosis was firstly attributed to relatively high levels of trypsin inhibitors (Gatehouse et al, 1979), but subsequently it was demonstrated that the resistance was in fact caused by the presence of variant vicilins (Macedo et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1970's, screening of the cowpea germplasm collection at the International Institute of Tropical Agriculture (Ibadan, Nigeria), allowed the identification of the first genotype highly resistant to C. maculatus, the cultivar TVu 2027 (Gatehouse et al, 1979), from which several other lineages such as IT81D-1032, IT81D-1053, IT81D-1045, and IT81D-1064 show different levels of resistance to the cowpea beetle were bred. The observed antibiosis was firstly attributed to relatively high levels of trypsin inhibitors (Gatehouse et al, 1979), but subsequently it was demonstrated that the resistance was in fact caused by the presence of variant vicilins (Macedo et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The observed antibiosis was firstly attributed to relatively high levels of trypsin inhibitors (Gatehouse et al, 1979), but subsequently it was demonstrated that the resistance was in fact caused by the presence of variant vicilins (Macedo et al, 1993). The defensive role of variant vicilins against the cowpea beetle was first reported from the genotype IT81D-1045, that is derived from the cultivar TVu 2027 and is also resistant to C. maculatus (Macedo et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…No presente trabalho, a baixa viabilidade de ovos no genĂłtipo TE96-290-12G, em teste sem chance de escolha, deve-se provavelmente Ă  presença de substĂąncias inibidoras da alimentação de C. maculatus, como exemplo a presença de proteĂ­na arcelina nos grĂŁos deste genĂłtipo. A presença de substĂąncias inibidoras de alimentação em carunchos Ă© relatada na literatura, a exemplo da arcelina que confere resistĂȘncia a Z. subfasciatus em feijoeiro (oriAni; lArA, 2000) e inibidores de tripsina responsĂĄveis pela antibiose em alguns genĂłtipos de feijĂŁo-caupi (GAtehouSe et al, 1989).…”
unclassified
“…In a similar study, Gatehouse et al (1979) suggested that the resistance in a crop of caupi (Vigna unguiculata) to the attack of the weevil Callosobruchus maculatus was due to the high concentration of inhibitors in this cultivar.…”
Section: Biological Applicationsmentioning
confidence: 96%